Performance Analysis of Uncoded and Coded 4XN Space Time Block Coded MIMO System Concatenated with MQAM in Rayleigh Channel - H. Belsare, M; P. B. Mane, Dr (International Journal of Engineering and Technology, 2018)
Wireless Communication using Multiple input and multiple output(MIMO) systems are achieving high data rates with increased diversity. This paper presents the performance analysis of half rate convolutionally coded 4x4, 4x3 and 4x2 STBC MIMO system concatenated with MQAM. System performance is analyzed for 4QAM, 8QAM and 16QAM in Rayleigh channel. It is observed that BER performance is better for 4x4 system as compared with other schemes. Results show that BER performances of employed coded 4x4 system is improved over uncoded system in Rayleigh channel.Â